2013
DOI: 10.1007/s11046-013-9660-1
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Relapsed Chromoblastomycosis Due to Fonsecaea monophora: Antifungal Susceptibility and Phylogenetic Analysis

Abstract: Chromoblastomycosis is a chronic cutaneous and subcutaneous mycosis. The management of this infection continues to be challenging because there is no consensus on the therapeutic regimen. We report here a case of a 69-year-old male patient with cauliflower-like lesions on his left leg and foot. He had already been treated with itraconazole at a dose of 200 mg/day for 5 months, with mycological cure for all the affected areas. However, the lesions relapsed at both sites, and treatment with itraconazole was resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
5
10
0
Order By: Relevance
“…To date, the drugs presenting better results in the treatment are ITZ and TRB . The in vitro results obtained in this study confirms this information, where TRB and ITZ showed the lowest MICs for the majority of the isolates tested.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…To date, the drugs presenting better results in the treatment are ITZ and TRB . The in vitro results obtained in this study confirms this information, where TRB and ITZ showed the lowest MICs for the majority of the isolates tested.…”
Section: Discussionsupporting
confidence: 85%
“…In this sense, the combined use of drugs can be an effective alternative, potentiating the action of the drugs and allowing the utilisation of reduced doses, minimising adverse effects . The combination of TRB and ITZ, often used in the clinic, was not synergic in in vitro assays, whereas TRB and AMB combination was synergistic for all genera, with the exception of E. spinifera , reinforcing results found in the literature …”
Section: Discussionsupporting
confidence: 78%
“…2,11 Chemotherapy options for CBM include various drugs such as ITZ, terbinafine (TBF), posaconazole, voriconazole, amphotericin B, 5-flucytosine, and ketoconazole. 12 Systemic antifungal therapy is validated for all patients whose initial lesions were not diagnosed at early stages nor surgically removed such as in our patient. The different treatment modalities available have not been compared in clinical settings and are mostly based on the successful therapies in reported cases.…”
Section: Discussionmentioning
confidence: 90%
“…Different antifungal susceptibility profiles may be observed among the different agents. F. monophora was reported to have a better response to treatment compared to F. pedrosoi , although recently resistance was verified in a case of chromoblastomycosis caused by F. monophora [13] , [14] . Therapy may depend on the etiological agent, size of the lesions, and on the patient’s health status and socio-economic parameters.…”
Section: Discussionmentioning
confidence: 98%